Glossophobia: A Cross-Sectional Assessment of Public Speaking Anxiety among Saudi Nursing Students - Deena Faisal Rayani; AlBatool Mohammed Bin Sallman; Reem Mohammed Barayan; Raghad Ahmed Maghrabi; Nahed Mohamed Morsy; Hala Ahmed Elsayes; Alaa Nabil Mahsoon; Loujain Saud Sharif (Nurse Media Journal of Nursing, 2023)
Background: Public speaking anxiety or glossophobia is common among college students, especially those studying in their non-primary language. Effective public speaking is considered an essential skill for nursing students to grasp as their future roles require it as patient advocates. Little is known about the effects of glossophobia amongst Arab students studying nursing in a second language (English).Purpose: This study aimed to examine glossophobia and its association with English oral presentations among Saudi nursing students in three academic levels.Methods: A correlational comparative study with a cross-sectional approach was conducted on a total of 209 baccalaureate level nursing students at a governmental, Saudi university. Convenience sampling was used with a comparison between three levels of student cohorts (second, third and fourth) of a single academic year. The data were collected using an online self-reported questionnaire consisting of three sections: a sociodemographic questionnaire, the Foreign Language Classroom Anxiety Scale (FLCAS), and the Personal Report of Public Speaking Anxiety (PRPSA). Data were analyzed using descriptive statistics, a one-way ANOVA, and Pearson correlation tests.Results: Nursing students had moderate anxiety on the FLCAS and PRPSA scales in all three academic years. There was a significant, moderate, and positive relationship between the two scales (r=0.450, p<0.01).Conclusions: Glossophobia among nursing students needs to be addressed. This study highlights a gap in current training where there is insufficient support, meaning that levels of anxiety remains unchanged across the trajectory of a nursing training program. Future research should explore culturally tailored strategies to decrease nursing students’ anxiety while building their confidence and self-esteem.